Development of Marketing Tools in Tourism as a Factor for Cooperation Enhancing Between the Primorye Territory and the Republic of Korea - Gataullina, Svetlana Y.; Kosolapov, Alexander B.; Shishkareva, Natalia Y. (International Review of Management and Marketing, 2017)
Tourism is a dynamically developing sector of the world economy which provides strong support to the foreign economic cooperation extension between different countries. Tourism development in the Primorye Territory is one of the strategic priorities of the regional policy It is considered as a factor for accelerating the region integration into the Asian-Pacific economic cooperation. One of the most dynamically developing tourism functions in the Primorye Territory is the cooperation with the Republic of Korea. The analysis of the tourist traffic between the Russian Federation and the Republic of Korea as well as factors effecting on the tourist's exchanges showed the necessity to improve marketing tools in the international tourism. The need to improve the tourism state regulations has been justified. Arranging of the regional tourism marketing as one of the significant factors determining the tourism activity effectiveness has been recommended. Keywords: foreign economic cooperation, marketing, tourism, Primorye Territory, Republic of Korea. JEL Classifications: F5, L9, Z3